Alocação de riscos e equilíbrio econômico-financeiro em contratos de gestão: o caso da fundação OSESP - Lopes, Marcelo de Oliveira (2016)
Partnerships between government and civil society institutions have proven an essential tool for the achievement of public policy. The 'National Program for Publicization', focusing on the non-exclusive public services, provided a good opportunity to make the management of those activities more flexible, calling the non-profit sector to play a leading role in the provision of public services in Brazil. The interaction between these agents creates the need for better understanding of their legal relationship and realign expectations and incentives, as well as better definition of risk allocation between partners. This paper analyzes the partnerships with social organizations in the culture sector in São Paulo. Particularly, the paper analyzes the Osesp Foundation management contract with the government, effective from 2005 to 2015. In this case, we analyzed opportunities and difficulties in the contractual relationship, the impact on the corporate governance of the institution, the risk allocation terms, its mitigation tools and economic and financial re-equilibrium.